Tinjauan Pustaka : Patofisiologi, Diagnosis, Tatalaksana, serta Strategi Pencegahan Otitis Eksterna - Khairunnisa, Kana; Agustina, Tri; Suwondo, Arsita Sri Devi; Rosita, Salsa Bela; Sari, Lutfita Singgih Intania; Fadhila, Jihan Nida (CV. Jasa Sukses Abadi, 2025)
Otitis externa is an infectious or noninfectious inflammation that occurs in the outer ear. Otitis externa can be acute, chronic, diffuse, and malignant caused by bacterial, fungal, or viral infections. The main predisposing factor is the swimming habit which can increase 5 times compared to people who do not swim. Factors that may increase the risk of infection, especially in humid climates or if there is narrowing of the ear canal. This article provides an in-depth review of the pathophysiology, diagnosis, management, and prevention strategies of otitis externa using the literature review method from reliable scientific sources. The data shows that the management of otitis externa involves the use of analgesics, topical antibiotics, oral antibiotics, and systemic antibiotics administered based on their classification, while prevention includes avoidance of precipitating factors and cerumen treatment. This conclusion emphasizes the importance of appropriate prevention strategies and accurate diagnosis to improve treatment outcomes and reduce the risk of recurrent infection.